Prestasi Belajar Ips Ditinjau Dari Kecerdasan Interpersonal Dan Minat Belajar Siswa - Maman Achdiyat (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2017)
Abstract: Research aims to determine the effect of Interpersonal intelligence and Interest in Learning together Learning Achievement Against Social Sciences in Junior High School in South Jakarta. If there is a positive and significant influence how strong the influence of interpersonal intelligence and interest in learning the achievements of Social Sciences. The research method is a survey with correlation and regression analysis techniques to determine the effect of each variable between, The sample is made the object of research is the students collected and analyzed. Descriptive statistics and data analysis requirements test before hypothesis test. From the results of data analysis and hypothesis testing research concluded that: (1). There is a significant influence interpersonal intelligence and interest in learning students' learning achievements of students of Social Sciences Junior High School in South Jakarta. This is evidenced by the obtained sig 0.001 <0.05 and F count = 7.960. (2) There is a significant effect on learning achievement interpersonal intelligence Social Sciences Junior High School students in South Jakarta. This is evidenced by sig 0.009 <0.05 and t = 2.686. (3). There is a significant influence student interest towards learning achievement of students of Social Sciences Junior High School in South Jakarta. This is evidenced by sig 0.007 <0.05 and t = 2.754. Keywords: Interpersonal intelligence, Interest in Learning, Learning Achievement, Social Sciences